Modulation of outer membrane vesicle-based immune responses by cathelicidins. Issue 16 (6th April 2022) - Balhuizen, Melanie D.; Versluis, Chantal M.; van Grondelle, Monica O.; Veldhuizen, Edwin J.A.; Haagsman, Henk P.
Highlights: OMVs from Bordetella bronchiseptica elicit immune responses in macrophages. Host Defense Peptides modulate the immune responses differently for sOMV and hOMVs. Signaling via human TLRs hTLR2, hTLR4, hTLR5 and hTLR9 is stimulated by OMVs. hTLR2- and hTLR4-mediated signaling can be downregulated by LL-37 and K9CATH. Uptake of OMVs plays a minimal role in eliciting an immune response in macrophages. Abstract: Antibiotic resistance is increasing and one strategy to prevent resistance development is the use of bacterial vaccines. For Gram-negative bacteria, natural outer membrane vesicles (OMVs) could be used for vaccine development. These vesicular structures are naturally produced by all Gram-negative bacteria and contain several antigens in their native environment. However, despite that the presence of lipopolysaccharide (LPS) may aid as intrinsic adjuvant, there is a risk that it may also cause undesired immune responses. Therefore, molecules to dampen LPS-induced toll-like receptor (TLR) 4 activation may be needed. Here host defense peptides (HDPs), like cathelicidins, can play an important role. They have been shown to interact with LPS and thereby neutralize LPS-induced TLR4 activation. However, there is currently no knowledge about neutralization in an OMV-based setting. Therefore, in this paper the immune modulating capacity of HDPs was investigated after macrophage stimulation with either spontaneous or heat-induced B. bronchiseptica OMVs. This revealed that the cathelicidins LL-37, CATH-2, PMAP-36 and K9CATH were able to modulate immune responses. Interestingly, immune modulation by these cathelicidins was different for spontaneous compared to heat-induced OMVs. Interaction studies revealed that the mode of binding of cathelicidins to OMVs slightly differed between OMV classes. Furthermore, TLR screening revealed that TLR2, 4, 5 and 9 were involved in stimulation of macrophages by OMVs, with TLR4-mediated activation being the most important pathway. Uptake of OMVs did not play a major role in macrophage activation. Taken together, this study shows how OMVs can activate macrophages and how cathelicidins may modulate these immune responses.